Flow dynamics of unsteady pyroclastic density currents (PDC) from Sunda ignimbrite, West Java, Indonesia - Ramadhan, Ilmi; Angkasa, Syahreza Saidina; Nugroho, Rio Priandri (Fakultas Teknik Geologi Universitas Padjadjaran, 2021)
Sunda Volcano is the one of several volcanoes in Indonesia which produced ignimbrite deposit from caldera forming eruption. Depending on the volume and considerable thickness of the deposits, Sunda ignimbrite might has been deposited with a variety of flow mechanisms. Heterogeneous deposition mechanism will heavily controlled by numerous parameters such as velocity, rheology, types of flow-boundary zone, or pre-existing topographic influence. According to the deposition parameters, Pleistocene Sunda ignimbrite transportation and deposition mechanisms are still unclear. Here we show detailed observations of each facies and the Unconformity Bounded Stratigraphic Units (UBSU) approach to determine the flow sub-units and flow mechanism of the Sunda ignimbrite. Overall, we found that Sunda ignimbrite consists of five different facies. Forestepping stacking pattern from Sunda ignimbrites also observed from stratigraphic correlation indicates that energy instability occurred during transport and deposition in the PDC. Waxing energy of PDC which occured is caused by the development of granular-flow and fluid-escape dominated flow-boundary zone at the base and body of emplaced PDC. Our results demonstrate how Sunda ignimbrite emplacement mechanism can be affects by pre-existing topography which developed during the effusive eruption of Sunda Volcano. Furthermore, we also found that Sunda ignimbrite deposition has been changed the topography into the gentler relief due to this forestepping pattern of each ignimbrite units. The study of Sunda ignimbrite facies can reveal suitable hazard mitigation and also use to characterize heterogenity in groundwater aquifers and geothermal reservoirs. Moreover, detailed facies analysis and UBSU could give us informations on how explosive eruption at 0.205 M.a take places on the southern flank of Sunda Volcano.